2003
DOI: 10.4049/jimmunol.170.10.5159
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 2 (TLR2) and TLR9 Signaling Results in HIV-Long Terminal RepeatTrans-Activation and HIV Replication in HIV-1 Transgenic Mouse Spleen Cells: Implications of Simultaneous Activation of TLRs on HIV Replication

Abstract: Opportunistic infections are common in HIV-infected patients; they activate HIV replication and contribute to disease progression. In the present study we examined the role of Toll-like receptor 2 (TLR2) and TLR9 in HIV-long terminal repeat (HIV-LTR) trans-activation and assessed whether TLR4 synergized with TLR2 or TLR9 to induce HIV replication. Soluble Mycobacterium tuberculosis factor (STF) and phenol-soluble modulin from Staphylococcus epidermidis induced HIV-LTR trans-activation in human microvessel endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
83
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 59 publications
6
83
0
3
Order By: Relevance
“…Once infection had been established (after 18 h), TLR2 and TLR4 were up-regulated in monocytes, probably to maintain the proinflammatory cytokine profile, which can also promote viral replication after provirus formation by activating NF-jB signaling in HIV-1-infected cells, similar to TLRs. [10][11][12][13][14] At the same time, TLR2 expression was downregulated in mDCs, the most important antigen-presenting cells, suggesting a viral mechanism to evade the immune response. 19 Thus, TLR activation may promote HIV-1 infection due to the effect of downstream signaling effectors on viral replication.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Once infection had been established (after 18 h), TLR2 and TLR4 were up-regulated in monocytes, probably to maintain the proinflammatory cytokine profile, which can also promote viral replication after provirus formation by activating NF-jB signaling in HIV-1-infected cells, similar to TLRs. [10][11][12][13][14] At the same time, TLR2 expression was downregulated in mDCs, the most important antigen-presenting cells, suggesting a viral mechanism to evade the immune response. 19 Thus, TLR activation may promote HIV-1 infection due to the effect of downstream signaling effectors on viral replication.…”
Section: Discussionmentioning
confidence: 89%
“…Subsequently, NF-jB can activate the HIV-1 genome by binding to the viral long terminal repeats (LTRs) in the provirus, even in models of HIV-1 latency. [10][11][12][13][14][15] TLRs are expressed in HIV-1 reservoir cells such as CD4 + T cells, macrophages, and DCs. [16][17][18][19] Various reports indicated that HIV-derived RNA can activate pDCs via TLR7 and TLR8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diferentes estudios sugieren que las infecciones por patógenos oportunistas, además de reducir la supervivencia de los pacientes con sida, al incidir directamente en la mortalidad, también representan un coestímulo para acelerar la pérdida de la función inmune y la progresión de la infección (6,7). De hecho, la presencia de infecciones oportunistas se ha asociado con activación de las células del sistema inmune, algunas de ellas infectadas con el VIH-1, promoviendo la replicación viral (8,9).…”
unclassified
“…De hecho, la presencia de infecciones oportunistas se ha asociado con activación de las células del sistema inmune, algunas de ellas infectadas con el VIH-1, promoviendo la replicación viral (8,9). Esto se traduce en un incremento de la carga viral en la circulación sistémica y en los diferentes tejidos (8), además de favorecer la diseminación de la infección, la apoptosis de varias subpoblaciones de células y la aparición de mutaciones en el genoma viral (7,10). Todo esto posibilita la evasión de la respuesta inmune y se puede asociar con cambios en el tropismo, en la patogenicidad, con la aparición de cepas resistentes a la terapia antirretroviral (2,11,12).…”
unclassified